Comparison of Inflammatory Cytokine Levels between Single-Port and Three-Port Thoracoscopic Lobectomy in the Treatment of Non-Small-Cell Lung Cancer. (30th July 2022) - Liang, Song; Yin, Xiao; Fu, Yu; Li, Xinglin; Zhu, Junchao; Xu, Ran
Abstract : Introduction . Thoracoscopic minimally invasive surgery is the main method for the treatment of lung cancer. The reduction of surgical trauma can effectively reduce the intraoperative and postoperative inflammatory reaction. The aim of the study is to compare the intraoperative and postoperative inflammatory reactions in patients with non-small-cell lung cancer (NSCLC) treated by single-port thoracoscopic surgery and three-port thoracoscopic surgery. Methods . A total of 68 NSCLC patients (stages I and II) of thoracoscopic surgery were selected and randomly divided into two groups where they received either single-port thoracoscopic surgery or three-port thoracoscopic surgery. Intraoperative and postoperative serum inflammatory markers (C-reactive protein, CRP; serum amyloid A protein, SAA; and interleukin 6, IL-6) were detected using the enzyme-linked immunosorbent assay. Results . The CRP level of the single-port group was significantly lower than that of the three-port group during surgery, the first day after surgery, and third day after surgery (P < 0.05 ). The level of IL-6 in the single-port group was significantly lower than that in the three-port group during surgery on the first and third days after surgery (P < 0.05 ). The level of SAA in the single-port group was also significantly lower than that in the three-port group on the first and third days after surgery (P < 0.05 ). Conclusion . Compared with three-port thoracoscopic surgery, single-port thoracoscopic surgery could reduce the inflammatory response and improve the recovery of NSCLC patients. Single-port thoracoscopic surgery is worthy of further promotion in the current treatment field of NSCLC in terms of reducing intraoperative and postoperative inflammatory reactions.